Peran Perempuan pada Usahatani Jagung di Kabupaten Tanah Laut - Alfa Riztri, Lucky; Krisnamurthi, Bayu; Nuraeni Muflikh, Yanti (Forum Agribisnis, 2025)
The Sustainable Development Goals (SDGs) launched by the United Nations (UN) pay special attention to gender issues in sustainable development, in SDG number 5 (five), namely gender equality. Therefore, the implementation of gender roles in sustainable development in Indonesia, especially in agribusiness development, is expected to reduce the level of gender inequality and empower all women. However, it was found that in some areas, women are limited in farming activities. Women are only involved in activities that require minimal resources, while their access to these resources and opportunities to participate in decision-making remain limited. This study aims to analyse the role of women in maize farming in Tanah Laut District in terms of three main aspects: role and participation, access to resources, and power in decision-making. The data used were primary and secondary data. Data analysis used descriptive qualitative and quantitative analyses using the Gender Dimensions Framework (GDF) approach. Quantitative analysis was conducted to test the significance of gender roles in maize farming using the independent T-test and Mann-Whitney test. The results show that women farmers can participate in all maize productive activities. The level of women's participation tends to be high in the activities of seeding, planting and harvesting. Women do not dominate any of the resources in the access and control profiles. However, based on farm management, in general, female farmers are not much different in terms of average planting area, number of harvests, productivity and price received compared to male farmers. Women and men have equal power in decision-making.